A Proposal of Standard Test Method for Frost Susceptibility of Soil - Ono, Т. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
. A recommendation of a standard test method for frost susceptibility of soil is proposed. The recommendation is required in order to have a design technique of common and equivalent quality not only in domestic but international practice. This topic is one of the essential and current objectives of Technical Committee 216 (ISSMGE) and has been discussing to the present. The purpose of the proposed recommendation test method is defined, different methods from several countries are compared, necessary and common articles are selected and some items are specified to discuss. It is expected that this proposal would take a role to be a draft suggestion to promote discussion and achieve a final recommendation.